Mechanical and geometrical study of 3D printed Voronoi scaffold design for large bone defects. (15th December 2021) - Herath, Buddhi; Suresh, Sinduja; Downing, David; Cometta, Silvia; Tino, Rance; Castro, Nathan J.; Leary, Martin; Schmutz, Beat; Wille, Marie-Luise; Hutmacher, Dietmar W.
Graphical abstract: Highlights: The Voronoi structure was used to design a patient specific bone scaffold matched to a critical-sized femur defect. Crucial surgical requirements and manufacturing constraints necessary to facilitate clinical translation of a scaffold design workflow have been accommodated. Geometrically comparing digitized 3D prints against their designed model is an effective method to assess the fabrication accuracy of scaffolds. Finite element method models were able to accurately predict the failure locations of the scaffold identified via the compression test. Abstract: The Voronoi design was utilized for a biodegradable patient-specific bone scaffold with macro pores (>4 mm) for the surgical treatment of a critical-sized bone defect. We have focused on the relationship between scaffold design and mechanical properties. Through a combination of experiments and simulations and have presented morphological and mechanical property maps of scaffold designs based on the Voronoi tessellation. Fused filament fabrication (FFF) was explored as the method of fabrication and prototypes were printed in commercial grade Polylactic Acid (PLA). The subsequent in-silico morphology assessment revealed that the pore sizes ranged from 4.0 to 11.8 mm with a total porosity of 71%. The morphological maps capture the distinct geometry shift between as-designed and as-manufactured scaffolds with an average agreement of 76% where most of the deviations were caused by complications innate to 3D printing. Finite element method models were developed to evaluate mechanical properties and the failure locations of the scaffold were accurately predicted, which was validated by the subsequent quasi-static compression test. This study revealed the potential of the Voronoi tessellation to design patient specific bone scaffolds with macro pore sizes that mimic trabecular bone geometry and concluded that FFF is a suitable method of fabrication for it.